Comparison of difloxacin, enoxacin, and cefazolin for the treatment of experimental Staphylococcus aureus endocarditis. - Boscia, J A (1988)
This study compared difloxacin administered orally, enoxacin administered orally, and cefazolin administered intramuscularly for the treatment of experimental Staphylococcus aureus endocarditis. Difloxacin significantly reduced bacterial counts of vegetations compared with enoxacin. This study demonstrated that difloxacin was significantly more effective than enoxacin and as effective as cefazolin for the treatment of S. aureus endocarditis in rabbits.